Waste Management and Enterprise Development in Slum Communities of Ado-Ekiti, Nigeria - Awosusi, Abike Ibidunni; Oriye, Olusegun; Owoeye, Julius Oluranti (Mediterranean Journal of Social Sciences, 2012)
This research explores the development of business enterprises through waste management in slum areas of Ado-Ekiti. The problem of waste disposal is a major concern in these areas of the city, being the reference point in this research work. Dirty environment would have been kept clean if only people were made to embrace the business opportunities in Waste Management as it puts money in their pockets. Both primary and secondary sources of data collection were accessed to gather relevant information for the work. The sample frame used is the total number of housing units in the six selected slum areas of the city. The total number of housing units in the area was 7858 out of which 2.5%, amounting to 200 housing units was selected as sample size with the aid of systematic random sampling. Findings in the study revealed the nature of waste generated in the area, ranging from food (domestic), paper, plastic and metal wastes. It was discovered also from the findings that very few, just about 1.0% of the respondents separate their wastes while 99.0% do not. This explains why Waste Management business is not embraced on a larger scale in Ado-Ekiti, except for a very few that are involved in scavenging, collection and those who work directly with the company in charge of street sweeping in collaboration with the State Waste Management Board. However, the encouragement of people becomes necessary in the establishment of business ventures in Waste Management Enterprise, which this research work sought to contribute to economic development in Waste Management in Ado-Ekiti.